The Effect of Labyrinth Games on the Concentration Ability of Children Aged 5-6 Years in Kindergarten - Desti Desti; Manto Manto (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to evaluate the effect of maze games on the concentration ability of children aged 5-6 years in kindergarten. Concentration is an important element in children's cognitive development that plays a crucial role in the learning process as well as daily activities. Labyrinth games were chosen as the object of research because they were considered able to stimulate children's focus and attention through interesting and challenging activities. This study used an experimental method with a pretest-posttest control group design. The subjects of the study consisted of kindergarten children aged 5-6 years, who were divided into two groups: an experimental group that was subjected to maze game treatment and a control group that was not. The instrument of this study is a concentration test adapted specifically for early childhood. The results showed a significant improvement in concentration ability in the experimental group compared to the control group. These findings indicate that maze play may be an effective alternative learning strategy for improving early childhood concentration. The implication is that educators can consider the integration of maze games in learning activities in kindergarten to support the development of children's cognitive abilities.